2016
DOI: 10.1186/s12889-016-3916-x
|View full text |Cite
|
Sign up to set email alerts
|

The burden of hypertension, diabetes mellitus, and cardiovascular risk factors among adult Malawians in HIV care: consequences for integrated services

Abstract: BackgroundHypertension and diabetes prevalence is high in Africans. Data from HIV infected populations are limited, especially from Malawi. Integrating care for chronic non-communicable co-morbidities in well-established HIV services may provide benefit for patients by preventing multiple hospital visits but will increase the burden of care for busy HIV clinics.MethodsCross-sectional study of adults (≥18 years) at an urban and a rural HIV clinic in Zomba district, Malawi, during 2014. Hypertension and diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
85
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 19 publications
13
85
4
Order By: Relevance
“…However, the prevalence in this study is slightly higher than those reported at Tikur Anbessa Specialized Hospital in Addis Ababa, Ethiopia (6.9%) [39] and University of Gondar Hospital, Northwest Ethiopia (5.1%) [40]. In addition, our report was higher than the reports of those studies carried out in other countries, including Uganda (4%) [41], Malawi (4.1% and 6.6%) [42,43] Zambia (5.0%) [44], but it is lower than the report of Senegal (14.5%) [45] and Tanzania (18.0%) [46]. The observed difference could be pertaining to variations in the lifestyle and HAART regimens or because of differences in the age distribution of the study participants.…”
Section: Discussioncontrasting
confidence: 83%
“…However, the prevalence in this study is slightly higher than those reported at Tikur Anbessa Specialized Hospital in Addis Ababa, Ethiopia (6.9%) [39] and University of Gondar Hospital, Northwest Ethiopia (5.1%) [40]. In addition, our report was higher than the reports of those studies carried out in other countries, including Uganda (4%) [41], Malawi (4.1% and 6.6%) [42,43] Zambia (5.0%) [44], but it is lower than the report of Senegal (14.5%) [45] and Tanzania (18.0%) [46]. The observed difference could be pertaining to variations in the lifestyle and HAART regimens or because of differences in the age distribution of the study participants.…”
Section: Discussioncontrasting
confidence: 83%
“…in Malawi (median ART duration = 11.6 years) and 22.6% in Uganda (median ART duration = 9.4 years). 32,35 Our findings suggest the higher prevalence of HTN among our cohort may be related to our cohort's longer duration on ART (median duration 12.1 years) and…”
Section: Discussionmentioning
confidence: 76%
“…27 The prevalence of HTN among HIV-infected adults on ART in other resource-limited settings ranges from 17% to 46%, which likely reflects differences in baseline characteristics, duration of infection and treatment. 1,[28][29][30][31][32][33][34][35][36] Two cohorts have similar ART duration as our study population but much lower prevalence of HTN: 19.3%…”
Section: Discussionmentioning
confidence: 99%
“…HIV/AIDS remains an infectious disease, even though the wider use of anti-retrovirals means that it can also be accurately described as a chronic disease. Furthermore, the relationship between this infectious but chronic condition and non-communicable diseases such as Type 2 diabetes and cardiovascular disease is very likely to be a feature of Malawi's changing epidemiological profile alongside urbanisation, ageing, changing diets and activity levels (Divala et al 2016;Narayan et al 2014;Levitt et al 2011;Kumwenda et al 2005;Bedell 2014). The role of infection is not confined to that played of HIV/AIDS.…”
Section: Creating Metabolic Knowledge In Malawimentioning
confidence: 99%